Implementing Wordwall to Promote Student Participation in Junior High School EFL Listening Activities - Alya Nurul Fadillah; Saskia Fitriana; Evatul Azizah; Dinda Khumayra; Ismail Rifqi Ubaidillah; Kenny Shania Lestari R. (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
Listening is an essential skill in English as a Foreign Language (EFL) learning; however, many students still face difficulties in understanding spoken English. Although Wordwall has been widely used in English learning, studies examining its implementation in EFL listening activities at the junior high school level remain limited. This study aimed to investigate how Wordwall was implemented in EFL listening activities and how students participated during the learning process. Employing a descriptive qualitative design, this study involved 32 seventh-grade students at SMP Negeri 13 Malang. Data were collected through classroom observation, semi-structured group interviews, and documentation, and were analyzed using Miles and Huberman’s qualitative data analysis procedures. The findings showed that Wordwall supported interactive listening activities by encouraging students to answer questions actively, collaborate in group discussions, maintain attention to audio materials, and respond positively during the lesson. Students also perceived Wordwall as enjoyable and helpful in supporting their focus and listening comprehension. These findings suggest that Wordwall may support a more interactive and student-centered listening environment in junior high school EFL classrooms. Practically, this study provides English teachers with an alternative digital learning medium to foster students’ participation and classroom interaction in listening instruction.